Determination of Permissible Short-Time Emergency Overloading of Turbo-Generators and Synchronous Compensators - V. A. Anischenko; V. A. Adamtsevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows that failure to take into account variable ratio of short-time emergency overloading of turbo-generators (synchronous compensators) that can lead to underestimation of overloading capacity or impermissible insulation over-heating.A method has been developed for determination of permissible duration of short-time emergency over-loading that takes into account changes of over-loading ratio in case of a failure.